2021
DOI: 10.1186/s13229-021-00439-5
|View full text |Cite
|
Sign up to set email alerts
|

Single-participant structural similarity matrices lead to greater accuracy in classification of participants than function in autism in MRI

Abstract: Background Autism has previously been characterized by both structural and functional differences in brain connectivity. However, while the literature on single-subject derivations of functional connectivity is extensively developed, similar methods of structural connectivity or similarity derivation from T1 MRI are less studied. Methods We introduce a technique of deriving symmetric similarity matrices from regional histograms of grey matter volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Traditionally, KL divergence between empirical distributions is calculated by a two-step approach: i) non-parametric estimation of the probability density functions (PDFs) of the observed data; and ii) computing the divergence using the approximated PDFs. However, the initial density estimation step of this approach is sensitive to many choices of parameters (Leming et al, 2021; Homan et al, 2019; Wang et al, 2016; Perez-Cruz, 2008). Extended to multiple dimensions, density estimation becomes especially problematic; for multivariate data with as few as three dimensions, standard non-parametric density estimators provide very poor results (Wang and Scott, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, KL divergence between empirical distributions is calculated by a two-step approach: i) non-parametric estimation of the probability density functions (PDFs) of the observed data; and ii) computing the divergence using the approximated PDFs. However, the initial density estimation step of this approach is sensitive to many choices of parameters (Leming et al, 2021; Homan et al, 2019; Wang et al, 2016; Perez-Cruz, 2008). Extended to multiple dimensions, density estimation becomes especially problematic; for multivariate data with as few as three dimensions, standard non-parametric density estimators provide very poor results (Wang and Scott, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the promise of MSNs, one key limitation is that they reduce the rich, vertex-level data from MRI-based cortical surface reconstructions to single summary statistics for each feature per region. While other work has explored structural similarity measured directly from vertex-level data, these methods were limited to the use of a single structural feature such as cortical thickness (Homan et al, 2019) or grey matter volume (Leming et al, 2021; Kong et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, in Wang et al (2021) , the maps of self-attention coefficients in the first and second layers are similar, indicating a consistent diagnosis. In Leming et al (2021) , the authors verified their suggested approach for classifying individuals with ASD and age-, motion-, and intracranial-volume-matched HCs by feeding a CNN the symmetric similarity matrix from regional histograms of estimated GM volumes. They also used graph-theoretic metrics on output CAMs to determine CNN’s favorite categorization regions, focusing on hubs.…”
Section: Highlighted Researchmentioning
confidence: 97%
“…Computer-aided design systems based on ML algorithms are highly time-consuming and complex to design. However, if the frontiersin.org Moridian et al 10.3389/fnmol.2022.999605 appropriate algorithms are selected, it can accurately diagnose ASD (Iglesias et al, 2017;Khosla et al, 2019;Hiremath et al, 2020;Leming et al, 2020Leming et al, , 2021. DL methods automatically perform the steps from feature extraction to classification.…”
Section: Challenges In Artificial Intelligence Algorithms In Diagnosi...mentioning
confidence: 99%